Analisis Perjalanan Rama pada Relief Ramayana Candi Prambanan untuk Konsep Naratif Animasi dengan Pendekatan Hero’s Journey - Setyawan, Alfan; Fijriani, Nissa (Institut Seni Indonesia Yogyakarta, 2024)
The Analysis of Rama’s Journey on the Ramayana Reliefs of Prambanan Temple for Animated Narrative Concept Using the Approach of Hero’s Journey . Reliefs of the Ramayana story can be found on the walls of the Shiva temple and the Brahma temple in Prambanan temple. The scene of each relief panel is well arranged so that a complete series of stories about Rama’s journey to save his wife Sinta is formed. The Ramayana relief of Prambanan temple is a narrative relief consisting of 76 scenes. The purpose of this research is to find the stages of the Ramayana storyline which is found in the Ramayana relief at Prambanan temple using the Hero’s Journey story structure. The research used qualitative research methods. Data were collected by observation, interviews, documents review, and literature studies. The collected data were analyzed, presented, discussed, and formed into conclusions as a result of the research.